The Difference in Neutrophil-Lymphocyte Ratio (NLR), Platelet-Lymphocyte Ratio (PLR), and Lactate Levels Between Sepsis and Septic Shock Patients Who Died in The ICU - Rachmawati, Dwi; Utariani, Arie; Notopuro, Paulus Budiono; Semedi, Bambang Pujo (Faculty of Medicine-Universitas Airlangga, 2023)
Introduction: Sepsis and septic shock are organ dysfunctions caused by the dysregulation of the body's response to infection and are the most common causes of death. Objective: This study aims to describe the neutrophil-lymphocyte ratio, platelet-lymphocyte ratio, and lactate levels in patients with sepsis and septic shock who died in the Intensive Care Unit (ICU). Methods: An observational retrospective study was conducted by examining the medical record data of sepsis and sepsis shock patients who were hospitalized in the ICU of Dr. Soetomo General Academic Hospital Surabaya from January to December 2019. Results: The study sample was 28 patients: 16 with sepsis and 12 with septic shock. Fifteen patients (53.6%) were women. The patients' mean age was 53.18 ± 13.61 years, and most patients (8 patients, 28.6%) belonged to the late adult age group (36-45 years). The most common comorbidities were diabetes mellitus and hypertension (30.8%). The highest incidence of infection in both groups occurred in the lungs (42.9%). Most of the patients had high SOFA scores, in the moderate (7-9) to severe (â‰¥ 10) category (39.3%). Almost all patients (82.1%) were treated for less than one week. The hematological examination within the first 24 hours showed a leukocyte value of 16,995 (Leukocytosis) and a platelet value of 279,500 (Normal). The NLR of septic shock patients (31.38±55.61) was higher than the NLR of sepsis patients (23.75±22.87). The PLR of septic shock patients (534.02±1000.67) was lower than the PLR of patients (802.93±1509.89). Lastly, the lactate levels in septic shock patients (3.84±1.99) were higher than in sepsis patients (1.97±1.06). Conclusion: There were no significant differences in the NLR and PLR values